An Investigation of Listening Problems Encountered by 1st Semester Students in Foundation of Listening Subjec - Gusnadi Gusnadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2019)
Gusnadi, penelitian yang diberi judul An Investigation of Listening Problems Encountered by 1st Semester Students in Foundation of Listening Subject bertujuan untuk menggambarkan dan mencari kesulitan-kesulitan mahasiswa pada belajar Foundation of Listening. Observasi, angket, dan list interview digunakan untuk mengumpulkan data secara qualitiatif. Adapun hasil temuan yang diperoleh antara lain; mahasiswa kesulitan memahami apa yang diperdengarka, mahasiswa mendapatkan kesuliatan pada saat mengambil inti dari apa yang diperdengarkan. Masalah lain adalah masalah teknis yang terkadang sangat mengganggu keberlangsungan pembelajaran Listening. Persiapan yang baik,pemeriksaan alat laboratorium bahasa, dan berlatih listening secara berkesinambungan akan memudahkan mahasiswa dalam belajar Listening.Kata Kunci: Deskriptif, Kesulitan Belajar ListeningAnderson, B. Marry. Brown, Dayna. And Jean, Isabella. 2012. Time to Listen: Hearing People on the Receiving End on International Aid. Cambridge, Massachusetts. CDA Collaborative Learning Projects.Brown, H. Douglas, 2000. Principles of Language Learning and Teaching Fourth Edition. Longman: San Fransisco.Creswell, W. John. 2012. Educational Research; Planning, Conducting and Evaluating Quantitative and Qualitative Research; 4th Edition. University of Nebraska-Lincoln. Pearson.Hamouda, Arafat. 2013. An Investigation of Listening Comprehensions Problems Encountered, by Saudi Students in the EL Listening Classroom; International Journal of Academic Research in Progressive Education and Development April 2013, Vol. 2, No. 2 ISSN: 2226-6348.Jackson, S.L. 2009. Research Methods and Statistics: A Critical Thinking Approach 3rd edition. Belmont, CA: Wadsworth.Nation I. S. P. and Newton Jonathan. 2009. Teaching ESL/EFL Listening and Speaking. Routledge. New York and London.Purdy, M. 1997 what is listening? In M. Purdy and D. Borisoff (eds.) Listening in Everyday Life. A Personal and Professional Approach. Lanham, MD: University Press of America.Richards, Jack. C. 2008. Teaching Listening and Speaking: From Theory to Practice. New York. United State of America: Cambridge University Press. Wilson, M. Suzzane and Peterson, L. Penelope. 2006. Theories of Learning and Teaching: What Do They Mean for Educators? National Education Association. Washington, DC.